The Nature and Causes of Modern Inflation in Russia ("Journal "U". Economy. Management. Finance.", 2020)
This article presents the dynamics of inflation in the period from 2008 to 2019 in Russia. Inflation is monetary and non-monetary in nature, can be both hidden and open. Accurate identification of the causes of inflation will help to correctly select measures to suppress it.
Keywords: inflation; the monetary and non-monetary nature of inflation; the causes of inflation; the rate of inflation; price increases; hidden and open inflation; anti-inflationary policies